KETERLAMBATAN PENGANGKUTAN SAMPAH DI TPS INDUK RAJABASA BANDAR LAMPUNG SEBAGAI ANALISIS DAMPAK SOSIAL DAN FORMULASI KEBIJAKAN PENGELOLAAN SAMPAH BERKELANJUTAN - Atikah Ramadhani; Ahmad Rama; Malikah Alya Azzahra; Annisa Dwi Lestari; Abdul Halim; Hasan Hariri (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
The delay in waste transportation at the Rajabasa Main Temporary Waste Disposal Site (TPS Induk Rajabasa) in Bandar Lampung has become a significant obstacle to achieving effective and sustainable waste management. This issue has led to waste accumulation, resulting in environmental pollution, public health risks, and declining community trust in public services. This study aims to analyze the factors causing delays in waste transportation, identify the social impacts experienced by surrounding communities, and formulate sustainable waste management policy recommendations. The research employed a qualitative approach with a case study design through field observations, in-depth interviews with waste management personnel and local residents, and analysis of relevant policy documents. The findings reveal that transportation delays are primarily caused by limited transportation fleets, increasing waste volumes, inadequate infrastructure, and weak operational coordination. These conditions have generated various social impacts, including disruptions to daily activities due to unpleasant odors, increased health risks, environmental degradation, and reduced public confidence in local government performance. Based on these findings, the study proposes policy formulations focused on improving transportation capacity, utilizing monitoring technologies, strengthening community participation, implementing circular economy principles, and enhancing coordination among stakeholders. The implementation of these policies is expected to support a more effective, sustainable, and environmentally sound waste management system